Effectiveness of Schema Therapy and Compassion-Focused Therapy on Emotional Self-Awareness, Hostile Attribution, and Critical Thinking in Adolescents with Binge Eating Disorder - Sepehrianazar, Firouzeh; Chitsaz, Mahdi (Applied Family Therapy Journal (AFTJ), 2025)
This study compares the effectiveness of schema therapy and compassion-focused therapy on emotional self-awareness, hostile attribution, and critical thinking in adolescents with binge eating disorder. The aim of this research was to evaluate the impact of these two therapies on improving the cognitive and emotional aspects of individuals. The research method was a semi-experimental study with a pretest-posttest and control group. The statistical population consists of adolescents with binge eating disorder in Azarshahr. The samples that were selected as available were randomly divided into two therapy groups (n=15). The first group received schema therapy, while the second group received compassion-focused therapy. To collect data, the Hostile Attribution Questionnaire (Arntz et al., 2003), the Self-Reflection and Insight Scale (Grant et al., 2002), and the Critical Thinking Questionnaire (Ricketts, 2003) were used. The results indicated that both therapies had a significant effect on increasing emotional self-awareness and reducing hostile attribution and critical thinking. However, compassion-focused therapy demonstrated a greater impact on reducing hostile attribution and improving critical thinking. The findings suggested that both approaches can be effective interventions for treating binge eating disorder in adolescents, with compassion-focused therapy being more effective in some aspects.